Acute Hepatic Failure Caused by Hepatitis B Virus Reactivation in Patients Receiving Immunomodulatory Agents for Autoimmune Diseases - Sung-Yu HSU; Cheng-Maw HO; Po-Huang LEE; Hong-Shiee LAI; Rey-Heng HU1 (Archives of Rheumatology, 2014)
Objectives: The increasing use of novel immunomodulators, such as rituximab, leflunomide and adalimumab in the treatment of autoimmune diseases may put hepatitis B virus (HBV) carriers at increased risk for reactivation and consequent hepatic failure. Patients and methods: We assessed 164 patients newly registered as liver transplant candidates at the National Taiwan University Hospital in 2010. Four patients (2.4%) also had underlying autoimmune disease and received immunomodulatory therapy which resulted in HBV reactivation and acute liver failure, which manifested as progressive hyperbilirubinemia and coagulopathy. The median time of survival of these patients was estimated using the Kaplan-Meier method. Results: All four patients were previously healthy HBV carriers with e antigen seroconversion. The mean peak alanine aminotransferase level was 3194.5±937.7 U/L. Entecavir was administered for an average of 39.8±10.5 days after the onset of the symptomatic hepatic dysfunction. Three patients who were experienced complications such as hepatic encephalopathy died. Only one patient survived liver failure. The median survival time after HBV reactivation and acute liver failure was 74.0 days (95% confidence interval, 31.9 to 116.1 days). The cumulative survival rate after HBV reactivation within three months was 25%. Conclusion: Prophylactic anti-HBV medication is recommended for HBV carriers with autoimmune diseases who are prescribed immunomodulatory agents for preventing catastrophic consequences such as acute liver failure caused by HBV reactivation.